Hockey lines for simulation‐based learning. (June 2015) - Topps, David; Ellaway, Rachel; Kupsh, Christine
Summary Background Simulation‐based health professional education is often limited in accommodating large numbers of students. Most organisations do not have enough simulation suites or staff to support growing demands. Context We needed to find ways to make simulation sessions more accommodating for larger groups of learners, so that more than a few individuals could be active in a simulation scenario at any one time. Moreover, we needed to make the experience meaningful for all participating learners. Innovation We used the metaphor of (ice) hockey lines and substitution 'on the fly' to effectively double the numbers of learners that can be actively engaged at once. Team players must communicate clearly, and observe keenly, so that currently playing members understand what is happening from moment to moment and incoming substitutes can take over their roles seamlessly. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Most organisations do not have enough simulation suites or staff to support growing demands </boxed-text> Implications We found that this hockey lines approach to simulation‐based team scenarios will raise learners' levels of engagement, reinforce good crew resource management (CRM) practices, enhance closed‐loop communication, and help learners to understand their cognitive biases and limitations when working in high‐pressure situations. During our continuing refinement of the hockey‐lines approach, we developed a number of variations on the basic activity model, with various benefits and applications. Both students and teachers have been enthusiastically positive about this approach when it was introduced at our various courses and participating institutions.